2019
DOI: 10.1016/j.synbio.2019.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Brocaeloid D, a novel compound isolated from a wheat pathogenic fungus, Microdochium majus 99049

Abstract: Microbes serve as the most important resource for drug discovery. During our screening for bioactive compounds from our natural products library, a pathogenic fungus, Microdochium majus strain 99049, from wheat was selected for further investigation. A new alkaloid named brocaeloid D (1), together with six previously characterized compounds (2–7) were identified. Compound 1 belongs to 4-oxoquinoline with C-2 reversed prenylation and a succinimide substructure. All the structures of these newly isolated compoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 56 publications
(65 reference statements)
0
9
0
Order By: Relevance
“…(22 E ,24 R )-6β-methoxyergosta-7,22-diene-3β,5α-diol 204, (22 E ,24 R )-6β-methoxyergosta-7,22-diene-3β,5α-diol 205, isolated from a pathogenic fungus, Microdochium majus strain 99 049, from wheat, showed moderate to weak anti-MRSA activity (MIC 25, 100 μg mL −1 , respectively). 110 The antimicrobial epidithiodioxopiperazine, gliotoxin 206, and bisdethiobis (methylthio)gliotxin 207, were isolated from the endophytic fungus Hypocrea virens , from Premna serratifolia , showed MIC 32–35 μg mL −1 against MRSA. 111 Terrenolide S 208, isolated from the endophytic fungus Aspergillus terreus isolated from the roots of Carthamus lanatus , displayed a potent activity towards MRSA with IC 50 2.29 μM.…”
Section: Controlling Multi-resistant Pathogens Using Terrestrial/micr...mentioning
confidence: 99%
“…(22 E ,24 R )-6β-methoxyergosta-7,22-diene-3β,5α-diol 204, (22 E ,24 R )-6β-methoxyergosta-7,22-diene-3β,5α-diol 205, isolated from a pathogenic fungus, Microdochium majus strain 99 049, from wheat, showed moderate to weak anti-MRSA activity (MIC 25, 100 μg mL −1 , respectively). 110 The antimicrobial epidithiodioxopiperazine, gliotoxin 206, and bisdethiobis (methylthio)gliotxin 207, were isolated from the endophytic fungus Hypocrea virens , from Premna serratifolia , showed MIC 32–35 μg mL −1 against MRSA. 111 Terrenolide S 208, isolated from the endophytic fungus Aspergillus terreus isolated from the roots of Carthamus lanatus , displayed a potent activity towards MRSA with IC 50 2.29 μM.…”
Section: Controlling Multi-resistant Pathogens Using Terrestrial/micr...mentioning
confidence: 99%
“…Spectroscopic analysis, including 1 H NMR, 13 C NMR ( Table 1 ), and DEPT, revealed that compound 1 contains three methyl groups, one of which is oxygenated, four methines, three saturated non-protonated carbons, and two ketone carbonyl carbons (δ C 175.94, δ C 194.36). Its NMR data closely resemble those of brocaeloid D [ 23 ], with the notable addition of a methoxy group (δ H 3.20/δ C 53.92). HMBC correlations confirmed the presence of a reversed prenyl group and differentiated compound 1 from brocaeloid D by the substitution of a succinimide substructure at C-14 with a methine at C-16, indicated by the methoxy group.…”
Section: Resultsmentioning
confidence: 81%
“…In addition, two sesquiterpene-xanthenone adducts, bisphenols I and J (39 and 40) (Figure 2), resistant to phytopathogenic fungi (Alternaria solani) were isolated from cultures of the potato endophyte fungus B. eleusines, and they showed potent inhibitory activity against A. solani with MIC values of 8 and 16 µg mL −1 , respectively [97]. The compounds leptosphaeric acid (50) and cillifuranone (51) (Figure 2) were isolated from the wheat endophytic fungus Microdochium majus 99049, which showed activity against the HUH-7 human hepatoma cell with IC 50 values at 80 µg/mL [96]. The compounds (+)-dehydrovomifoliol ( 52) and macrolactin A (53) (Figure 2) were isolated from the maize endophytic fungus Fusarium sp.…”
Section: Other Ketonesmentioning
confidence: 99%
“…Eight cytochalasins boerechalasins A-G (215-221) and compound 222 were isolated from the potato endophytic fungus B. exigua, and compound 220 exhibited moderate cytotoxicity against the MCF-7 cell line, with an IC50 value of 22.8 µM [120]. 8) were isolated from the wheat endophytic fungus M. majus 99049, and they showed weak inhibitory activity against the HUH-7 human hepatoma cell with IC50 values at 80 µg/mL [96]. The compound caffeine (226) was isolated from the maize endophytic fungus Fusarium sp.…”
Section: Other Alkaloidsmentioning
confidence: 99%